Between Memory and Hope : Readings on the Liturgical Year - Baldovin, John Francis; Johnson, Maxwell E. (Book collections on Project MUSE., 2000)
This anthology surveys the development and theology of the liturgical year in the order of its historical evolution: From Sabbath to Sunday"; "From Passover to Pascha" (Lent, Holy Week, Easter, and Pentecost); and "From Pascha to Parousia" (Epiphany, Christmas, and Advent). In addition, introductory essays on the meaning of the liturgical year and a short concluding section on the sanctoral cycle ("From Parousia to Persons") are also provided. While written as a companion to standard works in the field, beginning with graduate students in liturgy and seminarians, this book is intended for al - pastors, liturgists, catechists, religious educators - who seek to live according to the Church's theology of time as it is reflected in its calendar of feasts and seasons. Through feast and fast, through festival and preparation, the liturgical year celebrates the presence of the already crucified and risen Christ among us today. Between Memory and Hope shows that to live between past and future, between memory and hope, is to remember Christ's passion as we encounter his presence among us now and as we await his coming again in glory.